2008
DOI: 10.5664/jcsm.27353
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Related Symptoms in Four Latin American Cities

Abstract: SciEnTiFic invESTigATiOnSStudy Objectives: to estimate the prevalence of the most common sleep related symptoms (SRS) in the metropolitan areas of Mexico City, Montevideo (Uruguay), Santiago (Chile), and Caracas (Venezuela). Methods: The study consisted of a multistage cluster sampling of adults aged ≥ 40 years living in metropolitan areas. All participants completed a questionnaire on sleep related symptoms. Simplified respiratory polygraphy during sleep was conducted on 188 subjects from Mexico City. Obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
6
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 29 publications
5
48
6
17
Order By: Relevance
“…Insomnia has been reported in a wide range of figures between 5.2% and 66.4% in previous community‐based studies from different parts of the world. Different definitions have been used in these studies, which make comparison of the findings difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insomnia has been reported in a wide range of figures between 5.2% and 66.4% in previous community‐based studies from different parts of the world. Different definitions have been used in these studies, which make comparison of the findings difficult.…”
Section: Discussionmentioning
confidence: 99%
“…These consequences have substantial implications in both clinical practice and health economics, which are essential for planning and implementation of public health policies. Questionnaire‐based population studies have suggested high prevalence rates of sleep disorders . However, there have been substantial differences in findings depending on the sample characteristics, definitions and/or methodology used as well as differences in regional perceptions and management practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En un intento por aportar datos, Querales et al (11) informaron que la insuficiencia de sueño (registrada como 14 o más días de sueño o descanso insuficiente en el último mes) fue frecuente en un grupo de 85 mujeres adultas del estado Carabobo, Venezuela; además, la insuficiencia del sueño se encontró asociada significativamente a edad mayor de 40 años, exceso de peso, obesidad central, hipertrigliceridemia, relación colesterol total/HDLc elevada, relación triglicéridos/HDLc elevada y mayor riesgo de SM. Por su parte, al estudiarse la prevalencia de síntomas relacionados con el sueño en cuatro ciudades latinoamericanas (Ciudad de México, Montevideo, Santiago de Chile y Caracas) se encontró que los ronquidos, el insomnio y la somnolencia diurna mostraron frecuencias de 60,2 %, 34,7 % y 16,4 %, respectivamente (12) ; dicho trabajo no estuvo dirigido a demostrar asociaciones entre los síntomas estudiados y el RCM.…”
Section: Introductionunclassified
“…[12][13][14][15][16] Approximately 1 in 5 adults has at least mild OSA, and 1 in 15 adults has OSA of moderate or worse severity. 12,17,18 Initial research performed to evaluate the effect of mandibular setback surgeries on the pharyngeal airway space have been evaluated with lateral cephalograms. 7,[19][20][21][22][23][24] The limitations of a lateral cephalogram are that it is a static, 2-dimensional image that does not adequately represent the 3-dimensional volumetric (CBCT) has been used to evaluate the airway changes 3 dimensionally.…”
mentioning
confidence: 99%